Educational Guidelines To Overcome Obstacles Facing Pregnant Women Regarding The Performance Of Antenatal Exercises (Journal of Pharmaceutical Negative Results, 2023)
Background: Antenatal exercises aim at improving the physical and psychological well-being of pregnant women for labor and preventing pregnancy-induced pathologies by various physical means. Aim: The current study aimed to evaluate the effect of educational guidelines to overcome obstacles facing pregnant women regarding the performance of antenatal exercises. Research Design: A Quasi-experimental. Setting: The study was conducted at antenatal clinic at Al-Hussien Hospital- Al-Azhar University, Cairo, Egypt. Sample: (140) pregnant women repeating in antenatal clinic. Tools: Interviewing questionnaire sheet, Knowledge assessment sheet, Obstacles assessment sheet, Reported Practice assessment sheet, Satisfaction assessment sheet. Result: More than one-third (38.6%) of the studied pregnant women aged from 26 to 30 years old with mean ±SD= 24.81 ± 4.54. Less than two thirds (62.9%) were from rural areas. Two thirds (66.4%) of the studied pregnant women were housewives. Post educational guidelines there was a positive correlation between the total reported practices and the obstacles that facing the pregnant women regarding performance of antenatal exercises one month after educational guidelines. Conclusion: the current study concluded that, most of the studied pregnant women had an effective increase in practicing antenatal exercises after applying the educational guidelines about antenatal exercises. Recommendation: Developing an educational program, booklets, and guidelines for pregnant women in antenatal clinics about antenatal exercises.